Trace element concentrations in the moss Hypnum cupressiforme growing in a presumably unpolluted area. (September 2016) - Boquete, M.T.; Fernández, J.A.; Aboal, J.R.; Carballeira, A.; Martínez-Abaigar, J.; Tomás-Las-Heras, R.; Núñez-Olivera, E.
Abstract: In this study we determined the concentrations of As, Cd, Hg, Ni and Pb in samples of the moss Hypnum cupressiforme collected during 5 different sampling surveys (2006–2014) in a presumably unpolluted area in northern Spain (25 sampling sites). We then applied factor analysis (FA) to the data to explore the factors underlying the spatial and temporal variability in the concentrations. The percentage of variance explained by the FA ranged between 34 and 98%, and was usually higher than 70%. The FA yielded 5 factors that explained the variance in the concentrations of Cd, As, Hg and Pb in all sampling surveys and also a single factor that explained the variance in Hg and Pb concentrations in 2006. Although the lack of obvious sources of pollution in the study region (at least for the elements considered) suggests that most elements (except perhaps Ni) probably originated from long-range atmospheric transport, this would not explain the results of the FA. We suggest that rather than being due to the origin of the pollutants (as frequently assumed), the spatio-temporal variability in the concentrations of these elements is probably determined by a series of other factors: the physicochemical characteristics of the pollutants and of the moss binding surfaces, physiological processes (e.g. moss growth), and the characteristics of the sampling sites (e.g. vegetation cover, elevation, slope, aspect). We therefore conclude that the assumption that variations in element concentrations in moss tissues are due to the origin of the pollutants is an oversimplification that leads to erroneous interpretation of the results of biomonitoring studies with terrestrial mosses. Highlights: We determined the levels of pollutants in H. cupressiforme at a regional level. FA was used to explore their spatiotemporal variability. The origin of the pollutants was not the factor underlying this variability. Interpreting this variability as the pollutants' origin is an oversimplification. This leads to erroneous interpretation of the results of biomonitoring studies.